Essence of distinction: the ends, ways, and means of China’s military maritime quest - Erickson, Andrew S. (Frontiers in Political Science, 2024)
The People’s Republic of China (PRC)‘s rapid development of military maritime capabilities, and their harnessing under strong personalist paramount leader Xi Jinping to address ambitious national goals, is one of the most important subjects concerning great power security in the international system today. Understanding the key dynamics is thus inherently important. This article surveys Chinese-language publications, U.S. government analyses, and related research, and applies it to a larger framework that addresses both conceptual and empirical issues, considers comparative cases, and offers suggestions for further examination. Its findings are relevant to scholars and practitioners alike: China’s military maritime power radiates outward, backstopped by a land-based “anti-Navy.” Its Navy focuses on proximate seas—supported by Coast Guard, Maritime Militia, and survey vessel fleets; and extends into the farthest oceans. China’s sea forces and the strategy informing them has become progressively less distinctive with time and distance—trends continuing today. Herein lies one of the greatest strengths, and limitations, of Beijing’s dramatic military maritime development.